1988
DOI: 10.1021/bi00402a028
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P-450 C-M/F, new constitutive form of microsomal cytochrome P-450 in male and female rat liver with estrogen 2- and 16.alpha.-hydroxylase activity

Abstract: A new cytochrome P-450 isozyme, P-450C-M/F, has been purified from untreated rat liver microsomes. The purified preparation was electrophoretically homogeneous and contained 12-15 nmol of P450/mg of protein and had a minimum molecular weight of 48,500. The NH2-terminal amino acid sequence of P-450C-M/F was different from that of other P-450's. Immunoblot analysis of microsomes demonstrated that P-450C-M/F was present in the liver of untreated male as well as female rats. Treatment of rats with phenobarbital, 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1989
1989
2001
2001

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Many different isoforms of cytochrome P450 contribute to the 2-hydroxylation of estradiol in the liver. In rats, hepatic 2-hydroxylation of estradiol is catalyzed by cytochromes P450 1A2, 2B1/2B2, 2C6, 2C11, C-M/F (one or more members of the 2D family) and the 3A family (108,111,(113)(114)(115)(116)(117). In humans, cytochrome P450 1A2 and the 3A family are major enzymes for hepatic estrogen 2hydroxylation (112,(118)(119)(120)(121).…”
Section: -Hydroxylationmentioning
confidence: 99%
See 1 more Smart Citation
“…Many different isoforms of cytochrome P450 contribute to the 2-hydroxylation of estradiol in the liver. In rats, hepatic 2-hydroxylation of estradiol is catalyzed by cytochromes P450 1A2, 2B1/2B2, 2C6, 2C11, C-M/F (one or more members of the 2D family) and the 3A family (108,111,(113)(114)(115)(116)(117). In humans, cytochrome P450 1A2 and the 3A family are major enzymes for hepatic estrogen 2hydroxylation (112,(118)(119)(120)(121).…”
Section: -Hydroxylationmentioning
confidence: 99%
“…In male and female rats, the constitutively expressed hepatic cytochrome P450 C-M/F (thought to be a member of the 2D family; see ref. 116) has high activity for the 2-and 16αhydroxylation of estradiol and weak activity for 6α-, 6β-and 15α-hydroxylation of estradiol and for the conversion of estradiol to estrone (114). Cytochrome P450 2C11, a male specific isoform in rats, also catalyzes estrogen 16αhydroxylation (115) and liver microsomes from male rats catalyze the 16α-hydroxylation of estradiol to a much greater extent than liver microsomes from female rats (46).…”
Section: α-Hydroxylationmentioning
confidence: 99%
“…Other investigators have reported large amounts of E1 from E2 catalyzed by rat liver microsomes or purified CYPs (Sugita et al 1988;Watanabe et al 1991;Suchar et al 1995). 17β-HSD may also contribute to the interconversions of E1 and E2 by liver microsomes.…”
Section: Discussionmentioning
confidence: 94%